Simulation and Experimental Study of Multi-Particle Grinding Based on W-M Fractal Dimension - Shengfang Zhang; Zhiyi Leng; Qiang Duan; Mingjie Lu; Hongtao Gu; Ziguang Wang; Yu Liu (Machines)
Extended operation in complex environments characterized by high temperatures, pressures, and hydrogen exposure can lead to performance degradation for S32168 stainless steel welds of hydrogenation reactors, which significantly impacts the reliability of hydrogenation reactors. The impact of the grinding process on the grinding temperature and force of S32168 steel welds is studied in this paper based on the W-M fractal dimension. A multi-grain grinding simulation model was built, and grinding experiments were conducted. The results show that the grinding speed and depth increased as the grinding temperature increased. At a speed of 20 m/s and depth of 15 μm, the temperature peaked at 1073 °C. Increasing the grinding depth increased both the temperature and force, while increasing the speed increased the temperature but reduced the force. When the depth was 15 μm and speed was 20 m/s, the maximum temperature was 939.1 °C. At a 15 μm depth and 10 m/s speed, the normal and tangential grinding forces peaked at 11.68 N and 9.33 N, respectively. When the depth was 5 μm and the speed was 20 m/s, the grinding forces were the lowest with normal and tangential forces of 0.93 N and 1.72 N, respectively. Comparing the simulated and experimental temperature results through nine sets of experiments, the error range was 6.97–14.2% with an average of 9.37%. The simulation model effectively simulated the grinding process.